On Some Aspects of a Class of Discrete Probability Distributions - Das, Kishore Kumar; Purkayastha, Durba (International Journal of Statistical Sciences, 2025)
A class of functions has been introduced, leading to the introduction of corresponding class of discrete probability distributions. This includes several known as well as newly identified distributions as specific cases. Various distributional properties of these proposed distributions have been explored. Finally, the proposed distributions are fitted with a zero-truncated Poisson distribution to life data, and we also test their goodness of fit. IJSS, Vol. 25(1), March, 2025, pp 1-10